Penurunan Jasa (servis) Ekosistem Sebagai Pemicu Meningkatnya Perubahan Iklim Global - Katili, Abubakar Sidik (Jurnal Pelangi Ilmu, 2008)
The increasing of human population growth in the world causes increasingly height of requirement of goods and service. Accomplishment requirement of goods and service will be able to fulfilled if production of the goods and service is done on a large scale. Produce of goods and service requires input raw material obtained from exploitation resources of natures which there in ecosystem. The exploitation causes lowering ecosystem service and that thing experiences affecting globally. Global impact of which can be make a phenomenon, it is called global climatic change. In this article explained about some related of degradation ecosystem service and increasing global climate change. Some the things namely: understanding of global climate change, ecosystem and its component and process, degradation of service ecosystem as caused of human activity and degradation of ecosystem service can increase the global climate change. Conclusion in this article are the of global climate change happened, caused of human activity to exploiting source of natures and that activity done to increase product goods and service.